Karya Karawitan Citra Jalatarangga - I Putu Nanda Yoga Mayura; I Ketut Garwa; I Gede Yudarta (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
Citra Jalatarangga is a karawitan composition that is contextually inspired by the duality of freshwater and seawater springs found at Geger Beach. The duality embodied in this idea serves as the fundamental concept and is subsequently implemented in the formulation and structuring of Balinese karawitan performance techniques. This paper discusses the process of creating the work, the formal structure of the composition, and the aesthetic values contained within it. The karawitan composition Citra Jalatarangga employs three theoretical frameworks as analytical tools to describe the duality of the different water sources. Transformation theory is used to determine the form and structure of the composition, creativity theory serves as a reference in the creative process, and postmodern aesthetic theory functions as a guideline for applying aesthetic nuances to the work. The creative method used in the creation of Citra Jalatarangga is the Panca Sthiti Ngawi Sani method, which consists of five stages: the inspiration stage (ngawirasa), the exploration stage (ngawacak), the conception stage (ngarencana), the execution stage (ngawangun), and the production stage (ngebah). This work utilizes several instruments from the Gamelan Semara Dana as its expressive medium and is structured into three sections, each representing the duality of the water sources through different formulations and performance techniques. In addition, instrument arrangement, costume design, and lighting design also function as supporting aspects in the presentation of the work, which was staged at Wantilan Banjar Sawangan, Desa Adat Peminge.